1998
DOI: 10.1021/jp982696c
|View full text |Cite
|
Sign up to set email alerts
|

Bond Characterization of Metal Squarate Complexes [MII(C4O4)(H2O)4; M = Fe, Co, Ni, Zn]

Abstract: Tetraaqua metal squarate complexes, M(C 4 O 4 )(H 2 O) 4 , (M ) Fe, Co, Ni, Zn), are known to have a polymeric chain structure with C 4 O 4 2as a bridge (µ-2) ligand between two metal ions in the trans position. Each metal ion is bonded to two C 4 O 4 2and four water molecules. They are all isostructural with space group C2/c. A complete Ewald sphere of data is measured at 120 K up to 2θ of 100-120°using Mo KR radiation for each complex. Such carefully measured intensities are used to investigate the detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 67 publications
9
26
1
Order By: Relevance
“…In this respect, the Zr-C2 interaction differs from the image of intermediate interactions in molecules, which consist of the main group atoms (Bader, 1990). Similar observations for the metal-ligand bonds in the coordination compounds based on the experimental Laplacian were also reported by Smith et al (1997), Wang et al (1997), Hwang & Wang (1998), Lee et al (1999) and Macchi & Sironi (2003).…”
Section: Figuresupporting
confidence: 90%
“…In this respect, the Zr-C2 interaction differs from the image of intermediate interactions in molecules, which consist of the main group atoms (Bader, 1990). Similar observations for the metal-ligand bonds in the coordination compounds based on the experimental Laplacian were also reported by Smith et al (1997), Wang et al (1997), Hwang & Wang (1998), Lee et al (1999) and Macchi & Sironi (2003).…”
Section: Figuresupporting
confidence: 90%
“…The values of (r b ) for the Ni-N and Ni-O bonds may be compared with other recent studies on nickel(II) complexes, e.g. for trans-[Ni(NH 3 ) 4 (NO 2 ) 2 ], Ni-N = 0.65 (2), 0.76 (2) e Å À3 (Iversen et al, 1997); for [Ni(C 4 N 4 H 2 ) 2 ], Ni-N = 0.94 e Å À3 (Hwang & Wang, 1998); [Ni(C 4 O 4 )(OH 2 ) 4 ], Ni-O = 0.44, 0.47 e Å À3 (Lee et al, 1999); and a square-planar nickel(II) Schiff base complex, Ni-O = 0.581 (5), Ni-N = 0.522 (5), 0.644 (6), 0.711 (6) e Å À3 (Kožíšek et al, 2004). Our values of (r b ) are at the lower end of these, but are sufficiently large to suggest a significant shared interaction.…”
Section: Topological Properties Of the Metal-ligand Bondsmentioning
confidence: 99%
“…In view of these problems, and in light of subsequent experimental charge density studies on nickel(II) and cobalt(II) coordination compounds (Iversen et al, 1997;Hwang & Wang, 1998;Lee et al, 1999Lee et al, , 2002Ptasiewicz-Bak et al, 1999;Kožíšek et al, 2004), which showed very different features, we decided to re-investigate the charge density in complex (1), using a recent release of the XD software (Version 4.10). This version of XD has been shown in a number of studies (Lee et al, 2002;Macchi et al, 2001Macchi et al, , 2002Macchi & Sironi, 2003;Farrugia et al, 2003;Farrugia & Evans, 2005) to provide reliable charge densities from experimental data on transition metal complexes that are in good agreement with the densities from accurate quantum calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[7,19] Polymeric structures via µ-1,2-and µ-1,3-coordination have also been reported. [11,12,22,25] More recently, the trinuclear complex, [Cu 3 (pmap) 3 (µ 1,2,3 -C 4 O 4 )](ClO 4 ) 4 · 2H 2 O {pmap = bis[2-(2-pyridyl)ethyl][(2-pyridyl)methyl]-amine} with the µ-1,2,3-coordination mode has been structurally and magnetically characterized. [1] The different bonding modes in squarato-bridged metal(II) complexes are depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%